ENGLISH MEDIUM PUBLIC SCHOOLS IN NEPAL: A NEW LINGUISTIC MARKET IN EDUCATION - Saud, Mohan Singh (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
This article is the result of the pilot study of my PhD research project. It examines the views of the school principal, teachers, ethnic students and ethnic parents regarding the need and use of EMI along with its classroom practice. Nepal is a multilingual and multilicultural country with diverse geo-biological landscape. However, public schools in Nepal have been adopting English medium instruction as a new linguistic market in education, challenging the mother tongue based multilingual education policy of the government. This paradigm shift from Nepali as a medium of instruction (NMI) to English medium instruction (EMI) has raised controversy in the education system of Nepal. As this study found, there has been a growing demand of parents of EMI seeing English as a linguistic capital in the global socio-economic market and they have taken it as economic investment in education. A noticeable contradiction to the successful introduction of EMI in public school education is the tendency for there to be a gap between EMI policy and classroom practice. Teachers were found to have used bi-/trilingual language policy in the classroom neglecting the spirit of EMI. It seems that EMI public schools in Nepal need clear framework for the effective implementation of the spirit of English medium in the multilingual classroom contexts.